PRECONDITIONING AS PROTECTION AGAINST ISCHEMIC MYOCARDIAL INJURY - M. G. Shurygin; I. A. Shurygina; N. N. Dremina; O. V. Kanya (Acta Biomedica Scientifica, 2013)
The article discusses the phenomenon of metabolic adaptation to ischemia after repeated episodes of transient reduction in myocardial perfusion. It is shown that the phenomenon of ischemic preconditioning is to significantly improve the stability of the ischemic tissue and reperfusion injury that occurs after a few brief episodes of ischemia-reperfusion. Thus ischemic preconditioning is a multifactorial phenomenon, as implemented through adaptation to changes in the intracellular cascade of metabolic conditions and the restructuring of the myocardium with increased tolerance to its lower perfusion. The use of external actions aimed at the individual links of the process or set of them, will improve the outcomes of ischemic episodes, and better preservation of myocardial function in a compromised vascular bed. It is shown that one of the major incentives of ischemic preconditioning may make growth factors - FGF2 and VEGF. In this case, the protective effect is realized as by increasing the viability of myocardial contractile cells and vascular endothelial cells in myocardial ischemic damage of the hearth, and by neo-angiogenesis and improve the regenerative ability of mature cardiomyocytes.